2022
DOI: 10.30880/jtet.2021.13.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Strategies During Pandemic COVID-19: A Comparative Study of Indonesia and Malaysia in TVET Programs

Abstract: The purpose of this study is to gain an understanding of the teaching strategies used by lecturers in Indonesia and Malaysia during the COVID-19 pandemic. Many lecturers must consider the amount of teaching they can provide. The transition from offline to online learning, which is accompanied by extensive technological use, is extremely challenging. A survey study was designed using an online questionnaire. Thequestionnaire is including items on learning objectives, lesson materials, teaching and learning acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In our study, and similarly to Yuk-Kwang et al .’s (2021), the pandemic seems to have significantly impacted students' views of using digital technologies and learning in connection with companies. We envisage that these negative perspectives will turn positive once technologies are used effectively to maximise learning opportunities, as found in previous studies (Ana et al ., 2021; García de Paz and Santana, 2021).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our study, and similarly to Yuk-Kwang et al .’s (2021), the pandemic seems to have significantly impacted students' views of using digital technologies and learning in connection with companies. We envisage that these negative perspectives will turn positive once technologies are used effectively to maximise learning opportunities, as found in previous studies (Ana et al ., 2021; García de Paz and Santana, 2021).…”
Section: Discussionmentioning
confidence: 77%
“…(2020) compared two modalities of teaching delivery in VET (face-to-face and distance) and found no differences in the quality of teaching, even though face-to-face students performed better. A post-pandemic study in Indonesia and Malaysia revealed that online learning provides flexibility in teaching in VET (Ana et al ., 2021). After surveying VET teachers, García-de-Paz and Santana (2021) determined that the emergency situation facilitated building an environment for virtual education that would prove useful beyond the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, e-learning allows students to study online, utilizing technology such as video, audio and other digital learning platforms [1], [26], [63]. The combination of these two methods can create an effective and efficient learning experience for students [7], [57], [34]. This systematic review will explore the latest studies on the use of collaborative learning and e-learning, highlight the benefits and challenges of implementing them, and provide recommendations for universities to optimize their use [23], [29].…”
Section: Introductionmentioning
confidence: 99%